2001
DOI: 10.1034/j.1600-0765.2001.036004237.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed infection of Porphyromonas gingivalis and Bacteroides forsythus in a murine abscess model: involvement of gingipains in a synergistic effect

Abstract: Several microorganisms including Porphyromonas gingivalis and Bacteroides forsythus have been implicated to be etiologically important agents of periodontal disease. In this study, we determined the ability of combinations of periodontopathogenic microorganisms to cause tissue destruction in a murine abscess model. Although all bacterial combinations used in this study produced larger abscesses than did monoinfection of each bacterium, the combination of P. gingivalis and B.forsythus showed a synergistic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 18 publications
3
105
0
1
Order By: Relevance
“…Co-infection with periodontopathic organisms including P. gingivalis and B. forsythus [20] and P. gingivalis and Treponema denticola [31] has been reported to induce a synergistic effect on the size of lesions in a murine model. Primary infection of mice with P. gingivalis and F. nucleatum also resulted in significantly greater lesion size compared with infection with P. gingivalis alone [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infection with periodontopathic organisms including P. gingivalis and B. forsythus [20] and P. gingivalis and Treponema denticola [31] has been reported to induce a synergistic effect on the size of lesions in a murine model. Primary infection of mice with P. gingivalis and F. nucleatum also resulted in significantly greater lesion size compared with infection with P. gingivalis alone [32].…”
Section: Discussionmentioning
confidence: 99%
“…While animal studies have demonstrated the pathogenicity of mono-infections of periodontopathogens such as P. gingivalis [13][14][15][16][17], in recent years, reports have been published on the effects of mixed microbial infections including P. gingivalis and A. actinomycetemcomitans [18], P. gingivalis and F. nucleatum [19] and P. gingivalis and B. forsythus [20] which resulted generally in increased levels of pathogenicity with a synergistic effect observed in the humoral and cellular host responses. In the human, F. nucleatum colonizes the plaque prior to P. gingivalis and high levels of F. nucleatum have been demonstrated in association with P. gingivalis as well as other bacteria associated with periodontal disease, such as B. forsythus, Prevotella intermedia and Eikenella corrodens [21].…”
Section: Introductionmentioning
confidence: 99%
“…Cells grown in broth media were harvested by centrifugation, suspended in PBS, and syringe-passaged 3 times to form an equal suspension. Absorbance of each suspension was measured at 600 nm, and their cell concentrations were adjusted to about 10 11 cells/ml according to protocols in previous manuscripts 32,33) . Mice were injected at sites on the dorsal area with 200l (about ‫01ן2‬ 10 cells) of each suspension or 200l of a mixed suspension of P. gingivalis 16-1 (100l; about ‫01ן1‬ 10 cells) and T. denticola ATCC 33520 (100l; about ‫01ן1‬ 10 cells).…”
Section: Inoculation and Abscess Examination In Mouse Skin Modelmentioning
confidence: 99%
“…the virulence properties of P. gingivalis are enhanced by interaction with F. nucleatum (Frias et al, 2001;Kinder & Holt, 1989;Kolenbrander & Andersen, 1987), T. denticola (Grenier, 1992;Ikegami et al, 2004), and T. forsythia (Yao et al, 1996). T. denticola and P. gingivalis display a symbiotic relationship in degrading proteins, utilisation of nutrients and growth promotion (Grenier, 1992;Grenier & Mayrand, 2001;Hollman & van der Hoeven, 1999;Kigure et al, 1995;Nilius et al, 1993;Yoneda et al, 2001). Interactions between T. forsythia and other bacteria such as members of the "red complex" result in synergistic mechanisms in alveolar bone loss and immune-inflammatory responses in rats (Kesavalu et al, 2007).…”
Section: Synergistic Virulence Expressionmentioning
confidence: 99%